Symbolic Use of Fruit Images in John Webster’s the Duchess of Malfi - Pant, Shiva Raj (SCHOLARS: Journal of Arts & Humanities, 2025)
The research article investigates the intended outcomes of a gustatory item- apricot on the human behaviors in John Webster’s play The Duchess of Malfi (1623). The eponymous character Duchess is seduced to have apricots so that her marital status is exposed. Initially, the Duchess is sworn not to remarry and asked to remain widow, later on she is found to have been married and pregnant. This exposure is facilitated by Webster’s fruit strategy. Informed by a guiding question- How does Bosola employ apricot for proving the pregnancy of Duchess? This study uses the gustatory evidences related to Duchess and Bosola. Using cross-case and within case analysis, a claim is reached. If Bosola, the spy had not been able to seduce Duchess offering apricots, the play would have taken a different route and there would not have been the possibility of the tragedy of The Duchess of Malfi. The instances where the apricot strategy is employed are taken as evidences and analyzed accordingly. The analytical framework consists of two directions: Consuming without paring: the dainties of Duchess and gullibility of Duchess: A Spanish fig for the imputation. In this framework, the favor of Duchess to the apricot and the imputation charged against Bosola, the spy are considered and a claim is yielded. The assertion as the outcome of the analysis can be stated as: the Duchess has fallen victim because of her unusual fascination to apricot and the imputation must be charged against Duchess and not against Bosola.